ASPEK GRAMATIKAL DAN LEKSIKAL PADA SURAT AN-NABA’ - Miftahul Jannah; M Mujabun (Al-Lahjah, 2020)
Al-Qur'an has beauty both in terms of structure and its meaning. Likewise, the letter -An-Naba 'has a connection between one verse and another which is packaged in beautiful and perfect literature on the grammatical and lexical aspects of this research. This research aims to describe the grammatical and lexical aspects of the An-Naba letter'. This research is a research library research (library research) using descriptive methods through a qualitative approach. Researchers are the main instrument because through researchers all data are collected and analyzed. The results showed that in the An-Naba letter 'there are many verses that have semantic meanings especially grammatical and lexical meanings. From the grammatical aspect, there is grammatical cohesion, grammatical processes and also grammatical meaning. Grammatical cohesion consists of references, substitution, ellipsis, and conjunctions. Grammatical processes consist of affixations, namely prefixes, confixes, and suffixes. The grammatical meaning consists of general syntactic meanings namely istifham, taukid, nafi, istitsna ', and tamanni. And the special syntactical meaning is the function of the subject and object chapters. In the An-Naba letter, there are also many lexical meanings such as word الجِبَالَ which means mountain in the seventh and eighth verses and also word الحَقُّ which means true.